(untitled) (Research, Society and Development, 2022)
This paper aims to map the agriculture and livestock sector in the municipality of Araçatuba, located in the interior of the State of São Paulo, highlighting it as a tool for developing public policies that enable sustainable local development. Descriptive statistics and Exploratory Data Analysis (AED) were used. It was noticed that the agricultural producer mostly produces with his own resources, has low educational level, and most of the agricultural establishments in the municipality are small properties, which is in line with the Brazilian reality. Moreover, the predominant characteristics of agricultural establishments in the municipality of Araçatuba showed that most make use of conventional cultivation of land, the use of tractors is concentrated in larger establishments, along with agricultural equipment and pesticides with the predominant presence of family farming. Moreover, through the analysis of the characteristics of family farming, in comparison with the employer, through the land, technological, productive and social dimensions, it was found that the agricultural establishments focused on family farming are inferior in terms of area and technology, to the detriment of non-family farming focused on the agro-export market, with differences in land, social and technological productive factors. Finally, the statistically obtained results present positive data in the quantity of establishments active in agriculture and cattle-raising in the municipality, with emphasis on the production that contributes to the local supply of food by family agriculture, enabling the guidance of public policies for sustainable local development.